Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

Effects of starch nanoparticle-stabilized oleic acid emulsions and warm storage on the structural properties and starch digestibility of cooked rice - Ah-In Kim; Jae Young Park; Hyun Ho Bae; Sang Min Cha; Jong-Yea Kim; Ju Hun Lee; Eun Young Park; Hyun-Jung Chung (Food Research International, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Position-dependent selenium substitution in conjugated polymers for enhanced doping efficiency and thermoelectric performance - Bomi Kim; Sang Eun Yoon; Daeyeon Lee; Kwangil Jo; Hayoung Park; Seok In Lee; Kyungmin Kim; Min Thein Kyaw; Songhee Oh; Yuchan Heo; Yubhin Cho; Felix Sunjoo Kim; et al. (Chemical Engineering Journal, 2026)

Camellia sinensis (L.) mitigates copper oxide nanoparticles-induced lung inflammation and mucus production through suppressing MAPK signaling and MUC5AC - Woong-Il Kim; Seol Jang; So-Won Pak; Sin-Hyang Park; Ba-Reun Jin; Jong-Choon Kim; Changjong Moon; Joong-Sun Kim; Young-Kwon Cho; Taesoo Kim; In-Sik Shin (Molecular & Cellular Toxicology, 2026)

Morpho-Molecular Identification and Race Detection of Xanthomonas campestris pv. campestris Causing Black Rot Disease of Cabbage in Bangladesh - Arnab Goswami; Nafisa Akter Sadia; Pijush Kanti Jhan; Mahmudul Hasan; Tofazzal Islam; Ujjal Kumar Nath; Jong-In Park; Mehede Hassan Rubel (Australasian Plant Pathology, 2026)

Effect of root zone temperatures on seedling growth and nutrient uptake of Rehmannia glutinosa and Codonopsis lanceolata - Myong Sun Park; In Sook Park; Chang Yong Shim; Jong Myung Choi; Jong Pil Chun (Horticulture, Environment, and Biotechnology, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Synergistic enhancement of biomass-derived carbon anodes via TiO2 incorporation and nitrogen doping for high-performance lithium-ion batteries - Sasan Rostami; Farzaneh Ghasemipur; Jeevan Kumar Reddy Modigunta; Parisa Ahmadibarshahi; G. Murali; Yun Jong Seo; Young Ho Park; Seung Jun Lee; Soorathep Kheawhom; Milad Jourshabani; Byeong-Kyu Lee; Insik In (Chemical Engineering Journal, 2026)

Single-atom Cu-N/O aerogel nanozymes with dual enzymatic activities for point-of-care detection of multiple neurotransmitters - Thinh Viet Dang; Hyun Uk Lee; Ji-In Park; Jong-Seong Bae; Moon Il Kim (Chemical Engineering Journal, 2026)

Genome wide characterization and expression profiling of protein disulfide isomerase (PDI) gene family members in watermelon under cold stress - Nihar Sahu; Uzzal Somaddar; Ga-Eun Bok; Dhanasekar Divya; Ijaz Yaseen; Hoy-Taek Kim; Bo-Kook Jang; Jong-In Park (Genes & Genomics, 2026)

An update to the molecular identification of Xanthomonas campestris disease causing pathogens in crucifers – A mini review - Nihar Sahu; Masao Watanabe; Jong-In Park (Physiological and Molecular Plant Pathology, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Estimation of radiogenic heat production rate of deep subsurface rock mass using natural gamma-ray logs - Yeonguk Jo; Myungsun Kim; Yoonho Song; Tae Jong Lee; In-Hwa Park; Changhyun Lee; Eui-Seob Park (Geosciences Journal, 2026)

Biocontrol potential of beauvericin produced in a submerged culture of Beauveria bassiana 331R against cotton aphid Aphis gossypii - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Hyunbok Song; Seulki Kim; Tae Young Shin; Taek Su Shin; Soo‑Dong Woo; Hae Woong Park (BioControl, 2026)

Study on the hydrodynamic performance of toroidal propellers - Il-Rryong Park; Bu-Gun Paik; So-Won Jung; Je-in Kim; Myeong-Eun Kim; Jong-Woo Ahn; Sang-Hwan Kim (Ocean Engineering, 2026)

Evaluation and application of molecular marker sets for developing PHS-resistant wheat in Korea - Hyeonjin Park; Jin-Kyung Cha; So-Myeong Lee; Youngho Kwon; Woo-Jae Kim; Jong-Hee Lee; In-Jung Lee (Euphytica, 2026)
Pre-harvest sprouting (PHS) is a major constraint on wheat production in Korea, reducing grain quality and end-use value. To accelerate the development of PHS-resistant cultivars with improved agronomic performance, we employed a marker-assisted backcrossing (MABC) approach using molecular markers previously reported in the literature. For foreground selection, 81 molecular markers (74 KASP and 7 gel-based) targeting key genes related to PHS resistance, grain quality, and disease resistance were applied. Genome-wide background selection was conducted with 547 KASP markers to monitor recovery of the recurrent parent genome. Genotyping of 94 wheat accessions revealed distinct genetic clustering among domestic cultivars, introduced germplasm, and 1BL.1RS rye translocation lines, demonstrating the effectiveness of the marker set in capturing genome-wide diversity. Using MABC combined with speed breeding, three elite lines were developed by pyramiding favorable alleles from ‘Joongmo2008’ and ‘Tapdong’. Among them, ‘Milyang55’ exhibited strong PHS resistance (germination rate: 21.1%), desirable agronomic traits, and flour quality comparable to ‘Joongmo2008’. Donor genome proportions ranged from 25.5 to 43.0%, confirming efficient recovery of the recurrent parent genome. These results highlight the utility of integrating pre-selected molecular markers with MABC and speed breeding for the rapid development of elite wheat cultivars with improved PHS resistance and end-use quality.

Evaluation of total nitrogen stocks and burial rates in salt marshes and bare flats of Marine National Parks in South Korea - Inha Kwon; Taewoo Kim; Seo Joon Yoon; Shin Yeong Park; In Ok Lee; Dong-U Kim; Hosang Kim; Cheongjae Lee; Young Eun Kim; Changkeun Lee; Bong-Oh Kwon; Jung Kwan Ahn; et al. (Regional Studies in Marine Science, 2025)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Explainable AI-based evaluation of factors affecting heavy metal removal by microalgae-based adsorbents - Gyu-Ri Choi; Heejin Yang; Jong Ho Lee; Tan Runfa; In Sun Cho; Seong-Jik Park; Chang-Gu Lee; Jin-Kyu Kang (Journal of Applied Phycology, 2025)

Calcium-Rich Steel Slag as a Reactive Capping Material: Effects on Hydraulic Conductivity and Nutrient Attenuation in Cohesive Intertidal Sediments - Hee-Eun Woo; Valianto Rojulun Afif; Seongsik Park; Maheshkumar Prakash Patil; Ilwon Jeong; In-Cheol Lee; Jong-Oh Kim; Kyunghoi Kim (Journal of Marine Science and Engineering, 2025)
Fine-grained intertidal sediments are typically characterized by low hydraulic conductivity and high nutrient loads, conditions that hinder biogeochemical recovery and exacerbate eutrophication. This study examined the feasibility of calcium-rich steel slag (SS) as a multifunctional capping material for improving both physical and chemical properties of cohesive sediments. Short-term (24 h) column experiments with two slag dosages (25 g and 50 g) revealed that the higher dosage (SS50) increased sediment hydraulic conductivity by 113.2%, likely through Ca2+-mediated flocculation and enhanced pore connectivity. Phosphate (PO4-P) in pore water decreased by up to 64.1%, and effluent dissolved inorganic nitrogen (DIN) declined by 62.8%, indicating combined effects of Ca-driven precipitation, adsorption, and enhanced flushing. However, SS addition also raised pore water pH (to 11.8) and lowered redox potential, leading to transient phosphate release at the effluent boundary under reducing conditions. Cation analysis confirmed Ca2+ stability and Na+ reduction, suggesting improved sediment structural integrity. The results suggest that steel slag is a promising reactive capping material capable of enhancing permeability and controlling nutrient release in cohesive coastal sediments, yet further investigation into long-term ecological effects and dosage optimization is necessary.

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Evaluation of Brassica nigra germplasm for the development of pre-breeding resources to improve Brassicaceae - Uzzal Somaddar; Nihar Sahu; Sopheap Mao; Su-Won Kim; Ga-Eun Bok; Jong-In Park (Horticulture, Environment, and Biotechnology, 2025)

A Dual-Modality nanozyme Exploiting ROS-Responsive oxygen Catalysis for Precision NF-κB pathway Suppression in gouty arthritis - Sathiyamoorthy Padmanaban; Sree Samanvitha Kuppa; Omkar Sangabathula; Amal Babu; Adityanarayan Mohapatra; Sung Sun Kim; Hong Yeol Yang; Aravindkumar Sundaram; Hyung Keun Kim; Jong Keun Seon; In-Kyu Park (Chemical Engineering Journal, 2025)

Systemic toxicity and toxicokinetics study of self-assembled-micelle inhibitory RNA-targeting amphiregulin in cynomolgus monkeys following intravenous injection - Hyeon-Young Kim; Tae-Rim Kim; Sung-Hwan Kim; In-Hyeon Kim; Woong-Il Kim; Jun-Hong Park; Youngho Ko; Sungil Yun; Han-Oh Park; Jong-Choon Kim (Toxicological Research, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Quantification of growth and physiological characteristics in tolerant and sensitive watermelon lines under cold treatment - Ijaz Yaseen; Sanha Choi; Tariq Mukhtar; Jong-In Park; Hoy-Taek Kim (Horticulture, Environment, and Biotechnology, 2025)
Biochemical and physiological processes serve as key indicators for assessing the adverse effects of biotic and abiotic stressors in plants. Due to the limited and incomplete information on the growth, root morphology, and physiology of watermelon lines under cold stress in Korea, this study aimed to evaluate selected cold-tolerant lines (PI254744, SW20, and SW66) and cold-sensitive lines (PI525233 and SW54). The evaluation was based on root and shoot weight, root and shoot length, root morphology, photosynthetic pigments (chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids), and levels of proline, malondialdehyde (MDA), and soluble sugars in root and leaf samples collected at various time points. Two treatments were conducted: one at 28 °C as a control and one at 10 °C to simulate cold stress. The results revealed a decline in growth variables under cold stress compared to the control across all lines. However, the disintegration of root cellular structures and reduction in growth variables were less severe in the tolerant watermelon lines than in the sensitive ones. Under cold stress, proline, MDA, and soluble sugar levels increased in all watermelon lines relative to the control. Notably, the tolerant lines displayed elevated proline and soluble sugar levels, while the sensitive lines had higher MDA content. Furthermore, photosynthetic pigment levels were generally lower in all lines during cold treatment compared to the control, though the reduction was less pronounced in the tolerant lines than in the sensitive ones. A significant positive correlation was found between the percentage reduction in total chlorophyll content and the percentage reduction in growth variables. The lesser reduction in photosynthetic pigments, combined with higher levels of osmoprotectants (proline and soluble sugars) and lower MDA levels in the tolerant lines during cold stress, may suggest underlying mechanisms that warrant further biochemical and molecular studies to better understand cold resistance.

Development of advanced polyacrylonitrile fiber-based adsorbents for heavy metal ion removal through electron beam irradiation followed by amination - Minho Son; Jong-Seok Park; Sung-In Jeong; Byoung-Min Lee; Jae-Hak Choi; Joon-Pyo Jeun (Journal of Water Process Engineering, 2025)

In vitro study of silver nanoparticles-induced embryotoxicity using a rat whole embryo culture model - Woong-Il Kim; So-Won Pak; Se-Jin Lee; Sin-Hyang Park; In-Sik Shin; Changjong Moon; Wook-Jun Yu; Sung-Hwan Kim; Jong-Choon Kim (Toxicological Research, 2025)

Transcriptome-Based Prediction of the Toxicity of the Marine Biotoxin Okadaic Acid in Human Vascular Endothelial Cells - Jong Hee Kim; Jeong-In Park; Yewon Kim; Mira Park; Jang Kyun Kim; Young-Seok Han; Youn-Jung Kim (Ocean Science Journal, 2025)

Chitosan-gallic acid conjugate edible coating film for perishable fruits - Cho Rok Lee; Su Jin Lee; Tae In Kim; Kiramage Chathuranga; Jong Soo Lee; Sangsik Kim; Min Hee Kim; Won Ho Park (Food Chemistry, 2025)

Simple synthesis of K/P co-doped graphitic carbon nitride to enhance photocatalytic performance under simulated solar irradiation - Jong-Min Lee; Youn-Jun Lee; Jong Ho Lee; Runfa Tan; Jin-Sil Kim; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Environmental Research, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Molecular marker development for specific amplification of Xanthomonas campestris pv. campestris race 8 causing black rot disease in Brassica crops - Sopheap Mao; Yeo-Hyeon Kim; Nihar Sahu; Su-Won Kim; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of General Plant Pathology, 2025)

UV photoreduction-driven heterogeneous fenton-like process: Long-term reactivation of fenton sludge-derived biochar and enhanced acetaminophen degradation - Heejin Yang; Sung-Hyo Jung; Jong Ho Lee; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Journal of Water Process Engineering, 2024)

Effect of activated carbon-based two-stage adsorption on biogenic amine reduction and quality of anchovy fish sauce at industrial scale - Jung-Jin In; Kil Bo Shim; Jong Bong Lee; Yeon Joo Bae; Ga Yeon Kwon; Hyo Rim Lee; Sunhyun Park; Suk Kyung Sohn (Food Chemistry, 2024)

Metabolic-methane mitigation by combination of probiotic Escherichia coli strain Nissle 1917 and biochar in rumen fluid in vitro fermentation of dairy cow - Jeongkuk Park; Min-Jin Kwak; Min-Geun Kang; Dae-Yeon Cho; Jong Nam Kim; In-Geol Choi; Younghoon Kim (Journal of Environmental Chemical Engineering, 2024)

Genome wide identification of BBP/BPC transcription factor in tomato and its expression profiling in response to abiotic stress - Antt Htet Wai; Dhanasekar Divya; Jong-In Park; Lae-Hyeon Cho; Dohyeon Kim; Md Mustafizur Rahman; Chang-Kil Kim; Mi-Young Chung (Plant Biotechnology Reports, 2024)

A systematic review and BMD modeling approach to develop an AOP for humidifier disinfectant-induced pulmonary fibrosis and cell death - Donghyun Kim; Yusun Shin; Jong-In Park; Donghyeon Lim; Hyunjoon Choi; Seongwon Choi; Yong-Wook Baek; Jungyun Lim; Younghee Kim; Ha Ryong Kim; Kyu Hyuck Chung; Ok-Nam Bae (Chemosphere, 2024)

Breeding a black soybean line with green cotyledon free from lectin, KTI, P34, lipoxygenase, and stachyose - Sarath Ly; Byeong Eon Park; Sang In Shim; Min Chul Kim; Jin Young Moon; Jong Il Chung (Euphytica, 2024)

Highly visible-light-active sulfur and carbon co-doped TiO2 (SC-TiO2) heterogeneous photocatalysts prepared by underwater discharge plasma - Ha-Rim An; Chaehun Lim; Chung Gi Min; Byoungchul Son; Chang-Yeon Kim; Ji-In Park; Jong Pil Kim; Yesul Jeong; Jiwon Seo; Moonsang Lee; Jihyang Park; Young-Seak Lee; et al. (Chemosphere, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Graphitic-carbon-nitride-hydrophilicity-dependent photocatalytic degradation of antibiotics with different log Kow - Jong-Min Lee; Youn-Jun Lee; Yoo Jae Jeong; In Sun Cho; Eun Hea Jho; Seong-Jik Park; Chang-Gu Lee (Chemosphere, 2024)

Utilization of coffee waste as a sustainable feedstock for high-yield lactic acid production through microbial fermentation - Seulbi Kim; Jong-Cheol Kim; Yeong Yeol Kim; Jung Eun Yang; Hee Min Lee; In Min Hwang; Hae Woong Park; Ho Myeong Kim (Science of The Total Environment, 2024)

Correction to: Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Rapid analysis of insecticidal metabolites from the entomopathogenic fungus Beauveria bassiana 331R using UPLC-Q-Orbitrap MS - Jong-Cheol Kim; In Min Hwang; Ho Myeong Kim; Seulbi Kim; Teak Su Shin; Soo-Dong Woo; Hae Woong Park (Mycotoxin Research, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Characterization and distribution of black rot disease causing pathogen-Xanthomonas campestris pv. campestris races of the Jeju Island, South Korea - Jeong-Eui Hong; Hee-Jin Kim; Mohammad Rashed Hossain; Mehede Hassan Rubel; Nihar Sahu; Sopheap Mao; Jong-Goo Kang; Hoy-Taek Kim; Masao Watanabe; Jong-In Park (Journal of Plant Pathology, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Low frequency changes in CO2 concentration in East Asia related to Pacific decadal oscillation and Atlantic multi-decadal oscillation for mid-summer and early fall - Sang-Wook Yeh; Seung-Joo Ma; In-Hong Park; Hee-Jeong Park; Jong-Seong Kug (Science of The Total Environment, 2023)

Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics - Soo Hyeon Kim; Jiwon Seo; Yongcheol Hong; Yongwook Shin; Hea-Jong Chung; Ha-Rim An; ChangYeon Kim; Ji-In Park; Hyun Uk Lee (Journal of Water Process Engineering, 2023)

Toll-like receptor 4 is a key regulator of asthma exacerbation caused by aluminum oxide nanoparticles via regulation of NF-κB phosphorylation - Je-Oh Lim; Woong-Il Kim; So-Won Pak; Se-Jin Lee; Sung-Hyeuk Park; In-Sik Shin; Jong-Choon Kim (Journal of Hazardous Materials, 2023)

Glucosinolates and Biotic Stress Tolerance in Brassicaceae with Emphasis on Cabbage: A Review - Md. Abuyusuf; Mehede Hassan Rubel; Hoy-Taek Kim; Hee-Jeong Jung; Ill-Sup Nou; Jong-In Park (Biochemical Genetics, 2023)

Impact of controlled nitrogen application in water solution on seedling growth, tissue and soil nutrient concentrations in vegetative propagation of strawberry - Saleha Farjana; In Sook Park; Jong Myung Choi (Horticulture, Environment, and Biotechnology, 2023)

Volcaniclastic sedimentation associated with trachytic volcanism in an oceanic intraplate volcano (Dokdo volcano, Republic of Korea) - Seon In Park; Jong Ok Jeong; Young Kwan Sohn (Bulletin of Volcanology, 2022)

Performance evaluation of a visual guidance patient-controlled respiratory gating system for respiratory-gated magnetic-resonance image-guided radiation therapy - Hyung Jin Choun; Jung-in Kim; Chang Heon Choi; Seongmoon Jung; Hyeongmin Jin; Hong-Gyun Wu; Eui Kyu Chie; Jong Min Park (Physical and Engineering Sciences in Medicine, 2022)

Improvement of germinability of lettuce seeds with drum-priming under high temperature condition - Jong-In Park; Dong-Myung Cho; Jeong-Hee Oh; Ju-Sung Cho; Nam-Jun Kang (Horticulture, Environment, and Biotechnology, 2022)

Subchronic Toxicity Evaluation of Aluminum Oxide Nanoparticles in Rats Following 28-Day Repeated Oral Administration - Sung-Hyeuk Park; Je-Oh Lim; Woong-Il Kim; So-Won Park; Se-Jin Lee; In-Sik Shin; Changjong Moon; Je-Hein Kim; Jeong-Doo Heo; Jong-Choon Kim (Biological Trace Element Research, 2022)

Comparison of treatment plans between static jaw and jaw tracking techniques in postmastectomy intensity-modulated radiation therapy - Seongmoon Jung; Jung-in Kim; Jong Min Park; Kyung Hwan Shin; Jin Ho Kim; Chang Heon Choi (Physical and Engineering Sciences in Medicine, 2022)

Dose calculation of 3D printing lead shield covered by biocompatible silicone for electron beam therapy - Ohyun Kwon; Hyeongmin Jin; Jaeman Son; Chang Heon Choi; Jong Min Park; Jung-in Kim; Seongmoon Jung (Physical and Engineering Sciences in Medicine, 2021)

In silico analysis and expression profiling revealed Rlm1′ blackleg disease-resistant genes in Chromosome 6 of Brassica oleracea - Arif Hasan Khan Robin; Gopal Saha; Jong-In Park; Rawnak Laila; Md Abdur Rahim; Mita Bagchi; Hoy-Taek Kim; Hee-Jeong Jung; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2021)

Phytoplankton succession during a massive coastal diatom bloom at Marian Cove, King George Island, Antarctica - Misa Jeon; José Luis Iriarte; Eun Jin Yang; Sung-Ho Kang; Youngju Lee; Hyoung Min Joo; In-Young Ahn; Jisoo Park; Gi-Sik Min; Sang-Jong Park (Polar Biology, 2021)

Changes in the chemical properties of coir dust with increasing aging time and development of a method for determining moderate aging degree - Yun Seob Kim; In Sook Park; Eunsoo Park; Byoung-Kwan Cho; Chiwon W. Lee; Jong Myung Choi (Horticulture, Environment, and Biotechnology, 2021)

Identification and characterization of carotenoid biosynthesis related genes in a novel dark skinned citrus mutant cultivar ‘Suneat’ - Md. Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2021)

In silico characterization and expression of disease-resistance-related genes within the collinear region of Brassica napus blackleg resistant locus LepR1′ in B. oleracea - Mostari Jahan Ferdous; Mohammad Rashed Hossain; Jong-In Park; Hoy-Taek Kim; Arif Hasan Khan Robin; Sathishkumar Natarajan; Manosh Kumar Biswas; Hee-Jeong Jung; Ill-Sup Nou (Journal of General Plant Pathology, 2020)

In-silico identification and differential expression of putative disease resistance-related genes within the collinear region of Brassica napus blackleg resistance locus LepR2’ in Brassica oleracea - Mohammad Rashed Hossain; Mostari Jahan Ferdous; Jong-In Park; Arif Hasan Khan Robin; Sathishkumar Natarajan; Hee-Jeong Jung; Hoy-Taek Kim; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)
Blackleg disease, caused by Leptosphaeria maculans, greatly affects the production of cabbage ( Brassica oleracea ). However, definitive R-gene(s) are yet to be identified in this crop. In contrast, a number of R-loci have been identified in A- or B-genome crops. Identification of few resistant cabbage genotypes indicates the presence of R-genes in this C-genome crop. High ancestral synteny between Brassica genomes suggests that the collinear regions of known A- or B-genome R-loci may also contain functional R-genes in the C-genome. Strong resistance was observed in the cotyledons of cabbage inbred line SCNU-98 against two L. maculans isolates, 03–02 s and 00–100 s. We investigated the collinear region of the Brassica napus blackleg resistance locus LepR2’ in B. oleracea since both isolates of L. maculans contain corresponding avirulence genes. The locus was collinear to a 5.8 Mbp genomic segment of B. oleracea chromosome C09 containing 13 genes that have putative disease resistance-related domains. High expression of genes Bo9g117290 and Bo9g111510 against isolate 00–100 s, and high expression of genes Bo9g126150 and Bo9g111490 against both isolates in the resistant-line SCNU-98 indicate their putative roles in blackleg resistance, which remained to be functionally verified. This work enhances our understanding of R-gene-mediated resistance to blackleg in cabbage.

Influence of nutrient solution concentration on growth and tissue mineral content of Panax ginseng seedlings cultured in a root medium containing peat and perlite - Hyung Bum Park; Sang Yong Park; In Sook Park; In Bae Jang; Dong Yun Hyun; Chiwon W. Lee; Jong Myung Choi (Horticulture, Environment, and Biotechnology, 2020)

Development of powdery mildew race 5-specific SNP markers in Cucumis melo L. using whole-genome resequencing - Jewel Howlader; Yeji Hong; Sathishkumar Natarajan; Kanij Rukshana Sumi; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Molecular characterization of Acidovorax citrulli strain NIHHS15-280 causing bacterial fruit blotch disease in Korea and screening of resistance sources in melon - Md. Rafiqul Islam; Mohammad Rashed Hossain; Hoy-Taek Kim; Ujjal Kumar Nath; Md. Abuyusuf; Hee-Jeong Jung; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2020)

Molecular Identification and Expression Analysis of Carbonic Anhydrase VII in Pufferfish (Takifugu rubripes) - Kanij Rukshana Sumi; Soo Cheol Kim; Jewel Howlader; Md Rajib Sharker; Kap Seong Choi; Sang Ki Choi; Jong-In Park; Ill-Sup Nou; Kang Hee Kho (Ocean Science Journal, 2019)

Development of a marker for detection of Xanthomonas campestris pv. campestris races 1 and 2 in Brassica oleracea - Mehede Hassan Rubel; Sathishkumar Natarajan; Ujjal Kumar Nath; Michael Immanuel Jesse Denison; Jung Hee-Jeong; Kim Hoy-Taek; Park Jong-In; Nou Ill-Sup (Horticulture, Environment, and Biotechnology, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Intronic Sequence Variations in a Gene with Peroxidase Domain Alter Bolting Time in Cabbage (Brassica oleracea var. capitata) - Md. Abuyusuf; Ujjal Kumar Nath; Hoy-Taek Kim; Manosh Kumar Biswas; Jong-In Park; Ill-Sup Nou (Plant Molecular Biology Reporter, 2018)

Comparison of the antioxidant properties and flavonols in various parts of Korean red onions by multivariate data analysis - Mi Jin Park; Da Hye Ryu; Jwa Yeong Cho; In Jong Ha; Jin Seong Moon; Young-Hwa Kang (Horticulture, Environment, and Biotechnology, 2018)

Simultaneous analysis and exposure assessment of migrated bisphenol analogues, phenol, and p-tert -butylphenol from food contact materials - Joungboon Hwang; In-Ae Bae; Chanyong Lee; Subi Lee; Jae Chun Choi; Se-Jong Park; Jin-Hwan Hong; Gaeho Lee; MeeKyung Kim (Food Additives & Contaminants: Part A, 2018)

Perfluorinated compounds in food simulants after migration from fluorocarbon resin-coated frying pans, baking utensils, and non-stick baking papers on the Korean market - Heeju Choi; In-Ae Bae; Jae Chun Choi; Se-Jong Park; MeeKyung Kim (Food Additives & Contaminants Part B-Surveillance, 2018)

Identification of NBS-encoding genes linked to black rot resistance in cabbage (Brassica oleracea var. capitata) - Khandker Shazia Afrin; Md Abdur Rahim; Jong-In Park; Sathishkumar Natarajan; Hoy-Taek Kim; Ill-Sup Nou (Molecular Biology Reports, 2018)

Expression of anthocyanin biosynthesis-related genes reflects the peel color in purple tomato - Song-I Kang; Md Abdur Rahim; Khandker Shazia Afrin; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Horticulture, Environment, and Biotechnology, 2018)

Allelic variation in Brassica oleracea CIRCADIAN CLOCK ASSOCIATED 1 (BoCCA1) is associated with freezing tolerance - Hayoung Song; Hankuil Yi; Ching-Tack Han; Jong-In Park; Yoonkang Hur (Horticulture, Environment, and Biotechnology, 2018)

Gender affects prognosis of methicillin-resistant Staphylococcus aureus bacteremia differently depending on the severity of underlying disease - Chang Kyung Kang; Yee Gyung Kwak; Youngmi Park; Kyoung-Ho Song; Eu Suk Kim; Sook-In Jung; Kyung-Hwa Park; Wan Beom Park; Nam Joong Kim; Young Keun Kim; Hee-Chang Jang; Shinwon Lee; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Seismicity of the 2016 ML 5.8 Gyeongju earthquake and aftershocks in South Korea - Jimin Lee; Yonggyu Ryoo; Sun Cheon Park; Young Mo Ham; Jong Soo Park; Myeong Su Kim; Sang Mi Park; Hyen Geom Cho; Keun Su Lee; In Sun Kim; Hye Su Kim; Sunhee Bae (Geosciences Journal, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Expression Profiling of the CSDP Transcription Factor Gene Family Points to Roles in Organ Development and Abiotic Stress Response in Tomato (Solanum lycopersicum L.) - Khadiza Khatun; Ujjal Kumar Nath; Jong-In Park; Chang Kil Kim; Ill Sup Nou; Mi-Young Chung (Plant Molecular Biology Reporter, 2018)

Differential Expression under Podosphaera xanthii and Abiotic Stresses Reveals Candidate MLO Family Genes in Cucumis melo L - Jewel Howlader; Jong-In Park; Hoy-Taek Kim; Nasar Uddin Ahmed; Arif Hasan Khan Robin; Kanij Rukshana Sumi; Sathishkumar Natarajan; Ill-Sup Nou (Tropical Plant Biology, 2017)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Korean Brassica oleracea germplasm offers a novel source of qualitative resistance to blackleg disease - Arif Hasan Khan Robin; Nicholas J. Larkan; Rawnak Laila; Jong-In Park; Nasar Uddin Ahmed; Hossein Borhan; Isobel A. P. Parkin; Ill-Sup Nou (European Journal of Plant Pathology, 2017)

Genome-wide characterization and stress-responsive expression profiling of MCM genes in Brassica oleracea and Brassica rapa - Ashokraj Shanmugam; Arif Hasan Khan Robin; Senthil Kumar Thamilarasan; Harshavardhanan Vijayakumar; Sathishkumar Natarajan; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Journal of Plant Biology, 2017)

Ssanghwa-Tang, a traditional herbal formula, suppresses cigarette smoke-induced airway inflammation via inhibition of MMP-9 and Erk signaling - Je-Won Ko; Na-Rae Shin; Sung-Hyeuk Park; In-Chul Lee; Jung-Min Ryu; Young-Kwon Cho; Jong-Choon Kim; Chang-Seob Seo; In-Sik Shin (Molecular & Cellular Toxicology, 2017)

Discovery of candidate genes for heterosis breeding in Brassica oleracea L. - Seung-Yeon Jeong; Nasar Uddin Ahmed; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Acta Physiologiae Plantarum, 2017)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Directing human embryonic stem cells towards functional endothelial cells easily and without purification - Chang-Hyun Gil; Byeong-Seong Ki; Joseph Seo; Jong-Jin Choi; Hana Kim; In-Gul Kim; A.-Ra Jung; Won-Young Lee; Youngsok Choi; Kwideok Park; Sung-Hwan Moon; Hyung-Min Chung (Tissue Engineering and Regenerative Medicine, 2016)

Protective effects of garlic oil against 1,3-dichloro-2-propanol-induced hepatotoxicity: role of CYP2E1 and MAPKs - Je-Won Ko; Sung-Hyeuk Park; In-Chul Lee; Sang-Min Lee; In-Sik Shin; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Jeong-Doo Heo; Jong-Choon Kim (Molecular & Cellular Toxicology, 2016)

Alfin-like transcription factor family: characterization and expression profiling against stresses in Brassica oleracea - Md. Abdul Kayum; Jong-In Park; Nasar Uddin Ahmed; Gopal Saha; Mi-Young Chung; Jong-Goo Kang; Ill-Sup Nou (Acta Physiologiae Plantarum, 2016)

Genome-Wide Classification and Abiotic Stress-Responsive Expression Profiling of Carotenoid Oxygenase Genes in Brassica rapa and Brassica oleracea - Yonguk Kim; Indeok Hwang; Hee-Jeong Jung; Jong-In Park; Jong-Goo Kang; Ill-Sup Nou (Journal of Plant Growth Regulation, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Characterization and stress-induced expression analysis of Alfin-like transcription factors in Brassica rapa - Md. Abdul Kayum; Jong-In Park; Nasar Uddin Ahmed; Hee-Jeong Jung; Gopal Saha; Jong-Goo Kang; Ill-Sup Nou (Molecular Genetics and Genomics, 2015)

Anthocyanin biosynthesis for cold and freezing stress tolerance and desirable color in Brassica rapa - Nasar Uddin Ahmed; Jong-In Park; Hee-Jeong Jung; Yoonkang Hur; Ill-Sup Nou (Functional & Integrative Genomics, 2015)

Application of distributed KIneMatic wave STOrm Runoff Model (KIMSTORM) for flood simulation considering dam release in the NamHan river basin of Korea - In-Kyun Jung; Dong-Ryul Lee; Jong-Yoon Park; Geun-Ae Park; Seong-Joon Kim (Paddy and Water Environment, 2015)

Identification and expression analysis of WRKY family genes under biotic and abiotic stresses in Brassica rapa - Md. Abdul Kayum; Hee-Jeong Jung; Jong-In Park; Nasar Uddin Ahmed; Gopal Saha; Tae-Jin Yang; Ill-Sup Nou (Molecular Genetics and Genomics, 2015)

Kinome sequencing reveals RET G691S polymorphism in human neuroendocrine lung cancer cell lines - Nadiya Sosonkina; Seung-Keun Hong; Dmytro Starenki; Jong-In Park (Genes & Genomics, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Gordonibacter faecihominis sp. nov., isolated from human faeces - Jong-Sik Jin; Keun Chul Lee; In-Soon Park; Kwang Kyu Kim; Jong Seog Ahn; Yoshimi Benno; Masao Hattori; Jung-Sook Lee (Antonie van Leeuwenhoek, 2014)

감마선 조사에 의한 조직공학용 알긴산 나노섬유의 분해 영향 - Sung In Jeong; Jong-Bae Choi; Young Min Shin; Jong-Seok Park; Hui-Jeong Gwon; Young-Chang Nho; Seong Soo Kang; Youn-Mook Lim (Tissue Engineering and Regenerative Medicine, 2014)

감마선 조사에 의한 헤파린이 도입된 박테리아 셀룰로오스의 골조 직공학용 지지체로서의 개발 및 특성분석 - Sung In Jeong; Jin-Oh Jeong; Jong-Bae Choi; Young Min Shin; Jong-Seok Park; Hui-Jeong Gwon; Young-Chang Nho; Sung-Jun An; Man-Young Park; Youn-Mook Lim (Tissue Engineering and Regenerative Medicine, 2014)

Unveiling abundance and distribution of planktonic B acteria and A rchaea in a polynya in A mundsen S ea, A ntarctica - Jong‐Geol Kim; Soo‐Je Park; Zhe‐Xue Quan; Man‐Young Jung; In‐Tae Cha; So‐Jeong Kim; Kyoung‐Ho Kim; Eun‐Jin Yang; Young‐Nam Kim; Sang‐Hoon Lee; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary Polynyas, areas of open water surrounded by sea ice, are sites of intense primary production and ecological hotspots in the A ntarctic O cean. This study determined the spatial variation in communities of prokaryotes in a polynya in the A mundsen S ea using 454 pyrosequencing technology, and the results were compared with biotic and abiotic environmental factors. The bacterial abundance was correlated with that of phytoplankton, P haeocystis spp. and diatoms. A cluster analysis indicated that the bacterial communities in the surface waters of the polynya were distinct from those under the sea ice. Overall, two bacterial clades, P olaribacter (20–64%) and uncultivated O ceanospirillaceae (7–34%), dominated the surface water in the polynya while the P elagibacter clade was abundant at all depths (7–42%). The archaeal communities were not as diverse as the bacterial communities in the polynya, and marine group I was dominant (> 80%). Canonical correspondence analysis indicated that the oceanographic properties facilitated the development of distinct prokaryotic assemblages in the polynya. This analysis of the diversity and composition of the psychrophilic prokaryotes associated with high phytoplankton production provides new insights into the roles of prokaryotes in biogeochemical cycles in high‐latitude polynyas.

Expression of a functional recombinant chimeric protein of human hepatitis A virus VP1 and an Fc antibody fragment in transgenic tomato plants - Ho Yong Chung; Jong-Hwa Park; Hyun Ho Lee; Kyung Il Kim; Ha Young Chung; Garry Sunter; Jong Bum Kim; Wonyong Kim; In Sik Chung (Plant Biotechnology Reports, 2014)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

Metabolic versatility of toluene‐degrading, iron‐reducing bacteria in tidal flat sediment, characterized by stable isotope probing‐based metagenomic analysis - So‐Jeong Kim; Soo‐Je Park; In‐Tae Cha; Deullae Min; Jin‐Seog Kim; Won‐Hyung Chung; Jong‐Chan Chae; Che Ok Jeon; Sung‐Keun Rhee (Environmental Microbiology, 2014)
Summary DNA stable isotope probing and metagenomic sequencing were used to assess the metabolic potential of iron‐reducing bacteria involved in anaerobic aromatic hydrocarbon degradation in oil spill‐affected tidal flats. In a microcosm experiment, 13 C‐toluene was degraded with the simultaneous reduction of F e( III )‐ NTA , which was also verified by quasi‐stoichiometric 13 C‐CO 2 release. The metabolic potential of the dominant member affiliated with the genus Desulfuromonas in the heavy DNA fraction was inferred using assembled scaffolds (designated TF genome, 4.40 Mbp with 58.8 GC mol%), which were obtained by Illumina sequencing. The gene clusters with peripheral pathways for toluene and benzoate conversion possessed the features of strict and facultative anaerobes. In addition to the class II ‐type benzoyl‐ CoA reductase ( B am) of strict anaerobes, the class I ‐type ( B cr) of facultative anaerobes was encoded. Genes related to the utilization of various anaerobic electron acceptors, including iron, nitrate (to ammonia), sulfur and fumarate, were identified. Furthermore, genes encoding terminal oxidases ( caa 3 , cbb 3 and bd ) and a diverse array of genes for oxidative stress responses were detected in the TF genome. This metabolic versatility may be an adaptation to the fluctuating availability of electron acceptors and donors in tidal flats.

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Whole-genome sequence analysis of a Korean G11P[25] rotavirus strain identifies several porcine-human reassortant events - Van Thai Than; Jong-Hwa Park; In Sik Chung; Jong Bum Kim; Wonyong Kim (Archives of Virology, 2013)

Natronomonas gomsonensis sp. nov., isolated from a solar saltern - Tae-Yoon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Man-Young Jung; Sang-A Lee; Seong Woon Roh; Kyung June Yim; Takashi Itoh; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Magnetotelluric measurements along a reflection seismic profile: reprocessing and reinterpretation of MT data for crustal-scale electric resistivity structure in central Victoria, Australia - Seong Kon Lee; Tae Jong Lee; Toshihiro Uchida; In Hwa Park; Tim Rawling; Jim Cull; Yoonho Song (Geosciences Journal, 2013)

Neural substrates of acupuncture in the modulation of cravings induced by smoking-related visual cues: an FMRI study - O-Seok Kang; Song-Yi Kim; Geon-Ho Jahng; Hackjin Kim; Jong-Woo Kim; Sun-Yong Chung; Jun-Won Kim; Seung-In Yang; Hi-Joon Park; Hyejung Lee; Younbyoung Chae (Psychopharmacology, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Enhancement of resistance to soft rot (Pectobacterium carotovorum subsp. carotovorum) in transgenic Brassica rapa - Young-Jin Koh; Jong-In Park; Nasar Uddin Ahmed; Hee-Jeong Jung; Kwon-Kyoo Kang; Yoonkang Hur; Yong-Pyo Lim; Ill-Sup Nou (European Journal of Plant Pathology, 2013)

Hoeflea halophila sp. nov., a novel bacterium isolated from marine sediment of the East Sea, Korea - Man-Young Jung; Kee-Sun Shin; Suyeon Kim; So-Jeong Kim; Soo-Je Park; Jong-Geol Kim; In-Tae Cha; Mi-Na Kim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Effect of the size and surface charge of silica nanoparticles on cutaneous toxicity - Yoon-Hee Park; Hyun Cheol Bae; Yeonsue Jang; Sang Hoon Jeong; Ha Na Lee; Woo-In Ryu; Min Gun Yoo; Yu-Ri Kim; Meyoung-Kon Kim; Jong Kwon Lee; Jayoung Jeong; Sang Wook Son (Molecular & Cellular Toxicology, 2013)

Sequence polymorphisms in ribosomal RNA genes and variations in chromosomal loci of Oenothera odorata and O. laciniata - Jun Hyung Seo; Hyo Geun Bae; Da Hee Park; Beom Seok Kim; Jong Wook Lee; Jung In Lee; Dong Hyun Kim; Seok Won Lee; Bong Bo Seo (Genes & Genomics, 2013)

Effect of proton beam irradiation on germination, seedling growth, and pasting properties of starch in rice - Sang-Kuk Kim; Shin-Young Park; Kye-Ryung Kim; Jong-Hee Shin; Su-Yong Kim; Hak-Yoon Kim; In-Jung Lee (Journal of Crop Science and Biotechnology, 2012)

Melatonin attenuates gentamicin-induced nephrotoxicity and oxidative stress in rats - In-Chul Lee; Sung-Hwan Kim; Sang-Min Lee; Hyung-Seon Baek; Changjong Moon; Sung-Ho Kim; Seung-Chun Park; Hyoung-Chin Kim; Jong-Choon Kim (Archives of Toxicology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Enhanced expression of recombinant human cyclooxygenase 1 from stably-transfected Drosophila melanogaster S2 cells by dimethyl sulfoxide is mediated by up-regulation of nitric oxide synthase and transcription factor Kr-h1 - Kyung Hwa Chang; Jong-Hwa Park; Ha Young Chung; Jeon Hwang-Bo; Hyun Ho Lee; Do Hyung Kim; Yunjo Soh; In Sik Chung (Biotechnology Letters, 2012)

Expression of a recombinant chimeric protein of human colorectal cancer antigen GA733-2 and Fc fragment of antibody using a replicating vector based on Beet curly top virus in infiltrated Nicotiana benthamiana leaves - Kyung Il Kim; Ha Young Chung; Ki Hyun Yoo; Jong-Hwa Park; Hyun Ho Lee; Yeon Ju Soek; Ki Sung Ko; Hyung Sik Kang; Kyung Jin Lee; Doo-Byoung Oh; Young Hee Joung; In Sik Chung (Plant Biotechnology Reports, 2012)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Identification and characterization of stress resistance related genes of Brassica rapa - Nasar Uddin Ahmed; Jong-In Park; Hee-Jeong Jung; Mi-Suk Seo; Thamilarasan Senthil Kumar; In-Ho Lee; Ill-Sup Nou (Biotechnology Letters, 2012)

Identification and expression analysis of chitinase genes related to biotic stress resistance in Brassica - Nasar Uddin Ahmed; Jong-In Park; Mi-Suk Seo; Thamilarasan Senthil Kumar; In-Ho Lee; Beom-Seok Park; Ill-Sup Nou (Molecular Biology Reports, 2012)

A grid-based rainfall-runoff model for flood simulation including paddy fields - In-Kyun Jung; Jong-Yoon Park; Geun-Ae Park; Mi-Seon Lee; Seong-Joon Kim (Paddy and Water Environment, 2011)

Expression of a recombinant chimeric protein of hepatitis A virus VP1-Fc using a replicating vector based on Beet curly top virus in tobacco leaves and its immunogenicity in mice - Ho Yong Chung; Hyun Ho Lee; Kyung Il Kim; Ha Young Chung; Jeon Hwang-Bo; Jong Hwa Park; Garry Sunter; Jong Bum Kim; Dong Hwa Shon; Wonyong Kim; In Sik Chung (Plant Cell Reports, 2011)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

A very compact imaging spectrometer for the micro-satellite STSAT3 - Jun Ho Lee; Kyung In Kang; Jong Ho Park (International Journal of Remote Sensing, 2011)

Isolation and characterization of 28 polymorphic SSR loci from castor bean (Ricinus communis L.) - Kyoung-In Seo; Gi-An Lee; Kyung-Ho Ma; Do-Yoon Hyun; Yong-Jin Park; Jong-Wook Jung; Sok-Young Lee; Jae-Gyun Gwag; Chung-Kon Kim; Myung-Chul Lee (Journal of Crop Science and Biotechnology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

A new cloning strategy for generating multiple repeats of a repetitive polypeptide based on non-template PCR - Hun-Su Chu; Jung Ryum; Seo-Young Park; Byung-Gee Kim; Dong-Myung Kim; Jong-In Won (Biotechnology Letters, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Suppression of NH3 and N2O emissions by massive urea intercalation in montmorillonite - Kwang Seop Kim; Man Park; Choong Lyeal Choi; Dong Hoon Lee; Young Jin Seo; Chan Yong Kim; Jong Su Kim; Seok-In Yun; Hee-Myong Ro; Sridhar Komarneni (Journal of Soils and Sediments, 2011)

Extract of Poncirus trifoliata fruit reduces elevated serum IgE concentrations in chemically induced allergic model mice - Hyun Jung Park; Jong Bo Kim; In Song Han; Jin Hoi Kim; Bokyung Kim; Sung-Ho Kang; Ho-Sung Jung; Sang Ho Moon; Si Heung Sung; Hyuk Song (Horticulture, Environment, and Biotechnology, 2011)

Synthesis of double-layered rotavirus-like particles using internal ribosome entry site vector system in stably-transformed Drosophila melanogaster - Jong Min Lee; Ha Young Chung; Kyung Il Kim; Ki Hyun Yoo; Jeon Hwang-Bo; In Sik Chung; Jong-Hwa Park (Biotechnology Letters, 2011)

A general rule for synoptic-eddy feedback onto low-frequency flow - Jong-Seong Kug; Fei-Fei Jin; Juhyun Park; Hong-Li Ren; In-Sik Kang (Climate Dynamics, 2010)

Mutation in Wilted Dwarf and Lethal 1 (WDL1) causes abnormal cuticle formation and rapid water loss in rice - Jong-Jin Park; Ping Jin; Jinmi Yoon; Jung-Il Yang; Hee Joong Jeong; Kosala Ranathunge; Lukas Schreiber; Rochus Franke; In-Jung Lee; Gynheung An (Plant Molecular Biology, 2010)

Evaluation of the toxicological properties and hepatoprotective effects of PAI-N002, a mixture of herbal extracts, in rats - Sung-Hwan Kim; Jeong-Hyeon Lim; In-Sik Shin; Changjong Moon; Soo-Hyun Park; Sung-Ho Kim; Jung-Sik Lee; Eun-Hye Kwon; Jong-Choon Kim (Molecular & Cellular Toxicology, 2010)

Induction of Oxidative Stress in the Epididymis of Rats After Subchronic Exposure to Epichlorohydrin - In-Sik Shin; Jeong-Hyeon Lim; Sung-Hwan Kim; Kang-Hyeon Kim; Na-Hyeong Park; Chun-Sik Bae; Seong-Soo Kang; Changjong Moon; Sung-Ho Kim; Woojin Jun; Jong-Choon Kim (Bulletin of Environmental Contamination and Toxicology, 2010)

Experience-Dependent Plasticity of Cerebellar Vermis in Basketball Players - In Sung Park; Kea Joo Lee; Jong Woo Han; Nam Joon Lee; Won Teak Lee; Kyung Ah Park; Im Joo Rhyu (The Cerebellum, 2009)

A novel mutation in Hr causes abnormal hair follicle morphogenesis in hairpoor mouse, an animal model for Marie Unna Hereditary Hypotrichosis - In Cheol Baek; Jeong Ki Kim; Kyu-Hyuk Cho; Dal-Sun Cha; Jae-Woo Cho; Jong Keun Park; Chang-Woo Song; Sungjoo Kim Yoon (Mammalian Genome, 2009)

Anti-inflammatory effects of talosin A via inhibition of NF-kappaB activation in lipopolysaccharide-stimulated RAW264.7 cells - Youn-Hwan Hwang; Myoung-Seok Kim; In-Bae Song; Jong-Hwan Lim; Byung-Kwon Park; Hyo-In Yun (Biotechnology Letters, 2009)

Variation in the phenotypic features and transcripts of color mutants of chrysanthemum (Dendranthema grandiflorum) derived from gamma ray mutagenesis - Geung-Joo Lee; Sung Jin Chung; In Sook Park; Jong Suk Lee; Jin-Baek Kim; Dong Sub Kim; Si-Yong Kang (Journal of Plant Biology, 2008)

Involvement of p38 MAPK-mediated signaling in the calpeptin-mediated suppression of myogenic differentiation and fusion in C2C12 cells - Sung-Ho Kook; Ki-Choon Choi; Young-Ok Son; Kyung-Yeol Lee; In-Ho Hwang; Hyun-Jeong Lee; Wan-Tae Chung; Choon-Bong Lee; Jong-Sun Park; Jeong-Chae Lee (Molecular and Cellular Biochemistry, 2008)

Surfactin C inhibits Mycoplasma hyopneumoniae-induced transcription of proinflammatory cytokines and nitric oxide production in murine RAW 264.7 cells - Mi-Hyun Hwang; Zhi-Qiang Chang; Eun-Hee Kang; Jong-Hwan Lim; Hyo-In Yun; Man-Hee Rhee; Kyu-Shik Jeong; Seung-Chun Park (Biotechnology Letters, 2008)

15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) sensitizes human leukemic HL-60 cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis through Akt downregulation - Hoon Han; Sung-Won Shin; Chi-Yeon Seo; Hyuk-Chan Kwon; Jin-Yeong Han; In-Hoo Kim; Jong-Young Kwak; Joo-In Park (Apoptosis, 2007)

Knockout of a starch synthase gene OsSSIIIa/Flo5 causes white-core floury endosperm in rice (Oryza sativa L.) - Nayeon Ryoo; Chul Yu; Cheon-Seok Park; Moo-Yeol Baik; In Myoung Park; Man-Ho Cho; Seong Hee Bhoo; Gynheung An; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Cell Reports, 2007)

Antiangiogenic and Apoptotic Properties of a Novel Amphiphilic Folate-Heparin-Lithocholate Derivative Having Cellular Internality for Cancer Therapy - Mi Kyung Yu; Dong Yun Lee; Yoo Shin Kim; Kyeongsoon Park; Soo Ah Park; Dai Hyun Son; Gee Young Lee; Jong Hee Nam; Sang Yoon Kim; In San Kim; Rang Woon Park; Youngro Byun (Pharmaceutical Research, 2007)

Hypoxia-induced cell death of HepG2 cells involves a necrotic cell death mediated by calpain - Min-Ju Kim; Soo-Jin Oh; Seong-Hoon Park; Hong-Jun Kang; Moo-Ho Won; Tae-Cheon Kang; In Koo Hwang; Jae-Bong Park; Jong-Il Kim; Jaebong Kim; Jae-Yong Lee (Apoptosis, 2007)

Molecular characterization of mature pollen-specific genes encoding novel small cysteine-rich proteins in rice (Oryza sativa L.) - Jong-In Park; Hirokazu Hakozaki; Makoto Endo; Yoshinobu Takada; Hitoshi Ito; Masanori Uchida; Tomihiro Okabe; Masao Watanabe (Plant Cell Reports, 2006)

Identification of differentially expressed genes involved in spine formation on seeds ofDaucus carota L. (carrot), using annealing control primer (ACP) system - Jong-Sug Park; In Sun Kim; Moon Soo Cho; Shin Park; Sang Gyu Park (Journal of Plant Biology, 2006)

Surfactin C inhibits the Lipopolysaccharide-induced Transcription of Interleukin-1β and Inducible Nitric Oxide Synthase and Nitric Oxide Production in Murine RAW 264.7 Cells - Mi-Hyun Hwang; Jong-Hwan Lim; Hyo-In Yun; Man-Hee Rhee; Jae-Youl Cho; Walter H. Hsu; Seung-Chun Park (Biotechnology Letters, 2005)

Comparison and Analysis of the Complete Nucleotide Sequence of Foot-and-Mouth Disease Viruses from Animals in Korea and Other PanAsia Strains - Jae Ku Oem; Kwang Nyeong Lee; In Soo Cho; Soo Jeong Kye; Jong Hyeon Park; Yi Seok Joo (Virus Genes, 2004)

Genetic analysis of phosphomannomutase/phosphoglucomutase from Vibrio furnissii and characterization of its role in virulence - Sun-Hoi Kim; Sun-Hee Ahn; Jong-Hee Lee; Eun-Mi Lee; Nam-Hyun Kim; Kee-Jai Park; In-Soo Kong (Archives of Microbiology, 2003)

Dimethylsulfoxide and sodium butyrate enhance the production of recombinant cyclooxygenase 2 in stably transformed Drosophila melanogaster S2 cells - Kyung Hwa Chang; Jong Hwa Park; Youn Hyung Lee; Jong Ho Kim; Hyung Ok Chun; Je Hak Kim; In Sik Chung (Biotechnology Letters, 2002)

Production of recombinant endostatin from stably transformed Trichoplusia ni BTI Tn 5B1-4 cells - Jong Min Lee; Kyung Hwa Chang; Jong Hwa Park; Youn Hyung Lee; In Sik Chung (Biotechnology Letters, 2001)

OPTIMAL PRODUCTION AND IN VITRO ACTIVITY OF RECOMBINANT ENDOSTATIN FROM STABLY TRANSFORMED DROSOPHILA MELANOGASTER S2 CELLS - JONG HWA PARK; KYUNG HWA CHANG; JONG MIN LEE; YOUN HYUNG LEE; IN SIK CHUNG (In Vitro Cellular & Developmental Biology - Animal, 2001)

Production of recombinant rotavirus VP6 from a suspension culture of transgenic tomato (Lycopersicon esculentum Mill.) cells - In Sik Chung; Chang Heon Kim; Kyung Il Kim; Seong Hyun Hong; Jong Hwa Park; Ju Kon Kim; Won Yong Kim (Biotechnology Letters, 2000)

EXPRESSION OF RECOMBINANT ERYTHROPOIETIN IN STABLY TRANSFORMED DROSOPHILA MELANOGASTER S2 CELLS - JONG MIN LEE; JONG HWA PARK; JIN O PARK; KYUNG HWA CHANG; IN SIK CHUNG (In Vitro Cellular & Developmental Biology - Animal, 2000)

Production of recombinant endostatin from stably transformed Drosophila melanogaster S2 cells - Jong Hwa Park; Jong Min Lee; In Sik Chung (Biotechnology Letters, 1999)